Bardoxolone methyl improves survival and reduces clinical measures of kidney injury in tumor-bearing mice treated with cisplatin - Lauren E. Thompson; Stacey M. Tuey; Paola Garcia Gonzalez; Carly S. Chesterman; Courtney D. McGinnis; M. Scott Lucia; Lauren M. Aleksunes; Charles L. Edelstein; Melanie S. Joy (AAPS Open)
Abstract Objective Acute kidney injury (AKI) occurs in approximately one-third of patients treated with cisplatin and there is an outstanding need for mitigation strategies to decrease the frequency and severity of cisplatin-induced AKI. This study evaluated bardoxolone methyl (BARD) as a nephroprotectant in a multidose, tumor-bearing mouse model of cisplatin-induced AKI. BARD is an attractive therapeutic intervention due to its ability to protect against cisplatin-induced nephrotoxicity by activating Nrf2 and previous reports suggesting anti-tumorigenic effects. Methods In this study, CMT167 tumor-bearing mice were treated with four weekly doses of cisplatin with or without BARD and evaluated for survival, tumor growth, and clinical and histological measures of AKI. Kidney injury and/or function were evaluated by quantification of urinary kidney injury molecule-1 (KIM-1) and serum creatinine (SCr) levels as well as histopathology. Results Compared to mice receiving cisplatin alone, co-treatment with BARD significantly enhanced survival (p = 0.01). Moreover, BARD prevented elevation of urinary KIM-1 concentrations as early as one week after cisplatin treatment (p < 0.01) – a response that was observed throughout the 4-week study period. Cisplatin increased SCr concentrations by four weeks, which was prevented by BARD co-administration (p < 0.01). Cisplatin treatment significantly decreased tumor burden compared to vehicle-treated mice (p < 0.05 after two cisplatin doses) – a response that was not altered by BARD co-treatment. Conclusions Overall, the results of this study demonstrate that BARD has the potential to improve survival and reduce clinical measures of kidney injury in tumor-bearing mice treated with cisplatin, suggesting it could be used as a nephroprotectant to mitigate cisplatin-induced AKI.